ANALISIS KUALITAS MANAJEMEN BANDARA HALIM PERDANAKUSUMA DAN PENGARUHNYA TERHADAP KEPUASAN PELANGGAN TRANSPORTASI UDARA - B Sulistiyono, Bambang; Olivia, Sherly (JURNAL ILMIAH M-PROGRESS, 2016)
Since commercialization Halim Airport, very interesting passengers who use air transport services because of its position in the city center. The Number of passengers continues to increase from year to year. So the airport management is required to furnish the service that needs of passengers. An advanced security aspects task AVSEC. This study aims to examine the effect of AVSEC (Air Transport Service) personnel capabilities and sensitivity to customer satisfaction in Halim Perdanakusuma Airport, empirically, either partially or simultaneously. This research is a quantitative descriptive study. The total population are 132 people, divided into two population, namely 66 of AVSEC officers and 66 passengers. The sample surveyed by sex, education and age. Data were analyzed by using descriptive statistics such as the Average of scores and cross tabulations Test results show that the AVSEC officer had run of function and duty well but the level of user satisfaction aviation transport services have not run yet. Keywords: Ability, Sensitivity and Customer Satisfaction Air Transport